Spectrophotometric Determination of Levetiracetam by Developing Coloured Complexes with 2-Chlorophenylhydrazine and Anthranilic Acid - Muralikrishna, Ch.; Ramu, G.; Bikshambabu, A.; Venkata Rao, S.; Rambabu, C. (Asian Journal of Chemistry, 2011)
Two simple, sensitive, reproducible, rapid and economical spectrophotometric methods are described for the determination of levetiracetam (LVC) in bulk and formulations. Both the methods are based on the formation of coloured complexes of levetiracetam with 2-chlorophenylhydrazine (method-A) and anthranilic acid (method-B) in alcoholic medium. Under the optimized conditions the complexes show an absorption maximum at 560 and 485 nm with molar absorptivities of 1.130 × 104 and 7.110 × 104 mol-1 cm-1 and sandells sensitivities of 0.03546 and 0.03708 per 0.001 absorbance unit for method-A and method-B, respectively. The result of analysis has been validated statistically and by recovery studies. Both methods have been successfully applied for the assay of the drug in pharmaceutical formulations.